2015
DOI: 10.1007/s00432-015-2069-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment results of alternating chemoradiotherapy followed by proton beam therapy boost combined with intra-arterial infusion chemotherapy for stage III–IVB tongue cancer

Abstract: PBT-IACT for stage III-IVB tongue cancer has an acceptable toxicity profile and showed good treatment results. This protocol should be considered as a treatment option for locally advanced tongue cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 20 publications
0
34
1
4
Order By: Relevance
“…Second, this is the first study to report the planned sequential combination HT and IMPT. In previous studies, PBT was mainly used as a boost technique following or simultaneously with photon therapy, and also showed favorable toxicity and treatment results. Third, the acute toxicity profiles were, more or less, favorable following the HT/IMPT combination, while oncologic outcomes were all excellent and comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this is the first study to report the planned sequential combination HT and IMPT. In previous studies, PBT was mainly used as a boost technique following or simultaneously with photon therapy, and also showed favorable toxicity and treatment results. Third, the acute toxicity profiles were, more or less, favorable following the HT/IMPT combination, while oncologic outcomes were all excellent and comparable.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the incidence of ORN post RT or intensity-modulated radiotherapy (IMRT) was reported to range from 2% to 16% [29, 30]. Takayama et al [31] reported good treatment outcomes of PBT combined with intra-arterial chemotherapy for T3–4 tongue cancer (3-year OS of 87%). They also reported that, by using a spacer to fix the tongue and to avoid extra irradiation to the mandible, the incidence of ORN was only 3% (1 of 33 patients).…”
Section: Discussionmentioning
confidence: 99%
“…Огромную роль в лечении местнораспространённого плоскоклеточного рака полости рта играет сочетание внутриартериальной полихимиотерапии по методу Сельдингера и ретроградной суперселективной внутриартериальной полихимиотерапии в комбинации с лучевой терапией [12,13]. Существует два типа суперселективной внутриартериальной катетеризации: антеградная и ретроградная катетеризация.…”
Section: материалы и методыunclassified
“…В этом методе катетер вводился в целевую артерию через поверхностную височную артерию (STA) и / или затылочную артерию (ОА) ретроградно, при этом катетеры сохранялись до завершения лечения. Таким образом, метод HFT позволяет проводить ежедневную химиолучевую терапию [12,13].…”
Section: материалы и методыunclassified